On the order of growth of ring Q-homeomorphisms at infinity - Salimov, R. R.; Smolovaya, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For ring homeomorphisms f : ℝn → ℝn , we establish the order of growth at infinity.